A Novel Presentation of the Acute Airway: Anti‐IgLON5 Disease. (4th August 2020) - Chen, Jennifer; Vasani, Sarju
Abstract : Anti‐IgLON5 disease is a newly discovered novel sleep disorder at the crossroads of neurology and immunology. In addition to the underlying sleep disorder, anti‐IgLON5 manifests with progressive aerodigestive symptoms such as dysphagia, stridor, and vocal cord paresis in 90% cases and may present to the otolaryngologist. Herein we present a case of a patient with anti‐IgLON5 disease who presented to the hospital with an acute airway including marked stridor and respiratory failure requiring intubation and subsequently a tracheostomy. Laryngoscope, 131:E724–E726, 2021